2003
DOI: 10.1023/b:agen.0000021389.49659.31
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Vascular Endothelial Growth Factor (VEGF) and Thymidine Phosphorylase (TP) to Improve Angiogenic Gene Therapy

Abstract: To improve current angiogenic gene therapy with a vascular endothelial growth factor (VEGF)-encoding plasmid (Baumgartner et al. Circulation 1998; 97: 1114-23 [1]; Kusumanto et al. Fifth Annual Meeting of the American Society of Gene Therapy, Boston, 2002, Abstr. 621 [2]), we have generated a combination plasmid, encoding the VEGF gene and the thymidine phosphorylase (TP, also known as platelet-derived endothelial growth factor (PD-ECGF) or gliostatin (GLS)) gene: phVEGF165-TP.MB. Upon transfection in COS-7 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In summary, we have shown that endothelial cells grown in three-dimensional spheroid culture and co-implanted with hOBs into PBCB-scaffolds, organize in vivo into tubes and form dense functional vessel networks. [15][16][17], gene therapeutic approaches [18,19] or cell-based therapies using endothelial cells [9,10]. In this study, we have employed a three-dimensional endothelial cell spheroid system to improve in vivo vascularization in bone tissue constructs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have shown that endothelial cells grown in three-dimensional spheroid culture and co-implanted with hOBs into PBCB-scaffolds, organize in vivo into tubes and form dense functional vessel networks. [15][16][17], gene therapeutic approaches [18,19] or cell-based therapies using endothelial cells [9,10]. In this study, we have employed a three-dimensional endothelial cell spheroid system to improve in vivo vascularization in bone tissue constructs.…”
Section: Resultsmentioning
confidence: 99%
“…Without the generation of a functional vascular network, implanted cells will undergo apoptosis due to limitations in oxygen and nutrient supply. Multifarious strategies to induce therapeutic angiogenesis are described and comprise the use of various recombinant angiogenic growth factors such as VEGF and bFGF [15–17], gene therapeutic approaches [18, 19] or cell‐based therapies using endothelial cells [9, 10]. In this study, we have employed a three‐dimensional endothelial cell spheroid system to improve in vivo vascularization in bone tissue constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Without the generation of a functional vascular network, the implanted cells will undergo apoptosis due to limitations in oxygen and nutrient supply. Strategies to generate perfused microvessels in tissue engineering applications are multifarious and comprise the use of in vitro fabricated perfused microvessels [Neumann et al, 2003], the induction of host blood vessel formation by various angiogenic growth factors such as VEGF and bFGF [Pieper et al, 2002;Perets et al, 2003;Zisch et al, 2003] or gene therapeutic approaches to induce neoangiogenesis [Rebar et al, 2002;Bouis et al, 2003; for a review, see Dor et al, 2003]. In this study, we have employed a cell-based approach to improve angiogenesis in tissue-engineered constructs, using endothelial cells grown in form of three-dimensional spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are involved in the inner cell lining of all blood vessels [1,2]. It is important to mention that endothelial cells in response to tissue injury or hypoxic conditions can form new vessels through a differentiation process called angiogenesis [3,4].…”
Section: Introductionmentioning
confidence: 99%